Apologiae Sacerdotis dalam Ordo Missae: Studi Liturgi tentang Asal-Usul dan Evolusinya - Watu, Christianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
The purpose of this study is to investigate the origins of the personal prayers of the priest (apologiae sacerdotis) in the book of the Order of Mass (Ordo Missae) and how they have evolved to the present day. This study highlights two key aspects: first, the apologiae sacerdotis, and second, the Ordo Missae. The apologiae sacerdotis refers to certain prayers in the Mass that are recited only by the celebrant (priest or bishop), either silently or in a low voice. The Ordo Missae is a small section of the liturgical texts of the Roman Catholic Church found in the Missale Romanum. It contains the structure of the celebration, prayers, and rubrics used to celebrate Mass. This article analyzes the texts of the apologiae sacerdotis in several Ordines Missae that have developed from the 9th century to the present day. The research method employed is a literature study focusing on historical and comparative analysis. This study demonstrates that the apologiae sacerdotis influenced the formation of the structure of the Ordo Missae and that the current Ordo Missae is not purely Roman but rather a mixture of Roman rites and French-German adaptations. The inclusion of the apologiae sacerdotis in the Ordo Missae shows that the formulation and composition of liturgical books cannot be separated from cultural influences and the needs of the times.